EAT LIKE the ANIMALS : What Nature Teaches Us About Healthy Eating - Raubenheimer, David, 1960-; Simpson, Stephen J. (London : William Collins, 2020)
A New Scientist Best Book of 2020 How is it that a baboon and a blob of slime mould instinctively know what to eat for optimal health, balancing their protein, fat and carb intake in perfect proportions?
Includes index
Keywords: Nutrition; Proteins in human nutrition; Food supply -- Environmental aspects; Appetite -- Physiological aspects